2016 SID Honors and Awards. Issue 2 (1st March 2016) - Donelan, Jenny
Abstract : This year's winners of the Society for Information Display's Honors and Awards include Ho Kyoon Chung, who will receive the Karl Ferdinand Braun Prize for his contributions to the large‐scale commercialization and technology development of AMOLED displays; Seung Hee Lee, who will be awarded the Jan Rajchman Prize for his invention, product development, commercialization, and basic research of fringe‐field‐switching LCD devices; Nikhil Balram, who will receive the Otto Schade Prize for his outstanding contributions to image, video, and display processing technology and development of objective image‐quality benchmarking methodology that helped bring world‐class image quality to mainstream consumer displays; Shunsuke Kobayashi, who will be awarded the Slottow–Owaki Prize for his long‐term outstanding contributions to the education and training of students and professionals in LCD science and technology; and Anthony C. Lowe, who will receive the Lewis and Beatrice Winner Award for his outstanding and sustained contributions to the leadership and governance of the Society and the exceptional benefit provided to SID's members throughout his editorship of the Wiley/SID book series.